The association between gingival recession and buccal bone at maxillary anterior teeth. Issue 4 (8th October 2019) - D'Silva, Eric; Fraser, David; Wang, Bokai; Barmak, Abdul Basir; Caton, Jack; Tsigarida, Alexandra
Abstract: Background: Gingival recession and a thin or absent buccal plate occur frequently at maxillary anterior teeth and necessitate careful treatment planning to prevent future complications. However, the association between these two conditions is unclear and the ability of gingival recession to predict underlying buccal bone deficiencies is unknown. Therefore, the aim of this study is to use clinical and radiographic data to test this association and determine the influence of demographic and clinical parameters on both conditions. Methods: This investigation comprised a single‐center, retrospective study. Data were derived from periodontal examinations performed on 66 adult subjects. Corresponding cone‐beam computed tomography images were used to measure the width of buccal bone at two points along the root surface and the distance between the bone crest and cemento‐enamel junction (CEJ). Results were then analyzed to determine the association between the presence of gingival recession and the condition of radiographic buccal bone, as well as the relative contribution of demographic parameters and other clinical findings to gingival recession and buccal bone conditions. Results: Gingival recession was present at 32.9% of maxillary anterior teeth and was most common at canines, followed by lateral incisors and central incisors. Mean buccal bone widths were significantly less, and the distance between the CEJ and bone crest was significantly greater for teeth with recession. Accordingly, gingival recession was a significant predictor for buccal bone thickness <1 mm at the level of 4 mm apical to the CEJ (odds ratio 2.733, 95% confidence interval 1.644 to 4.543, P < 0.0001). Probing depths were related to the presence or absence of gingival recession, while patient sex, age, and the apico‐coronal height of the gingiva were related to buccal bone thickness. Conclusion: Within the limitations of this study, maxillary anterior teeth with pre‐existing gingival recession were more likely to have thin (<1 mm) buccal bone.